BIMBINGAN KARIER SEBAGAI UPAYA MENUMBUHKAN NILAI-NILAI KEWIRAUSAHAAN ISLAMI DI PONDOK PESANTREN ENTERPRENEUR AD DHUHA PAJANGAN BANTUL - Anggi Jatmiko (Sociocouns: Journal of Islamic Guidance and Counseling, 2022)
This research is motivated by some challenges and competition in an era of increasing globalization, especially in the economic field. If someone does not want himself to be alienated by the situation, then he must accomplish qualified skills to be able to compete. This condition has an impact on the behavior of some people who take shortcuts in competing. Many cheating acts are increasingly prevalent among entrepreneurs. Even though the Qur'an clearly states that Allah SWT hates those who cheat. Based on these conditions, career guidance is needed to foster entrepreneurial values for the nation's next generation. The purpose of this study is to examine in depth about the implementation of career guidance in an effort to grow the values of Islamic entrepreneurship in Pesantren (Islamic Boarding School) Entrepreneur Ad Dhuha. This research applied a field research, by describing the implementation of career guidance in fostering Islamic entrepreneurship values in Pesantren Ad Dhuha. Data sources were obtained from the founder of the Islamic Boarding School, caregivers and several students. The results showed that in growing Islamic entrepreneurship values in Pesantren applied career guidance services with entrepreneurship training and adjustment of business values, hard work, honesty, orderly administration and creating habit of Dhuha prayers. Performing Dhuha Prayer is the same as almsgiving. While Allah SWT promises that when someone sincerely presents part of his wealth, then Allah will multiply the reward and gift for him.